Identifying positively deviant elderly medical wards using routinely collected NHS Safety Thermometer data: an observational study. Issue 2 (16th February 2018) - Baxter, Ruth; Taylor, Natalie; Kellar, Ian; Pye, Victoria; Mohammed, Mohammed A; Lawton, Rebecca
Abstract : Objective: The positive deviance approach seeks to identify and learn from exceptional performers. Although a framework exists to apply positive deviance within healthcare organisations, there is limited guidance to support its implementation. The approach has also rarely explored exceptional performance on broad outcomes, been implemented at ward level, or applied within the UK. This study develops and critically appraises a pragmatic method for identifying positively deviant wards using a routinely collected, broad measure of patient safety. Design: A two-phased observational study was conducted. During phase 1, cross-sectional and temporal analyses of Safety Thermometer data were conducted to identify a discrete group of positively deviant wards that consistently demonstrated exceptional levels of safety. A group of matched comparison wards with above average performances were also identified. During phase 2, multidisciplinary staff and patients on the positively deviant and comparison wards completed surveys to explore whether their perceptions of safety supported the identification of positively deviant wards. Setting: 34 elderly medical wards within a northern region of England, UK. Participants: Multidisciplinary staff (n=161) and patients (n=188) clustered within nine positively deviant and comparison wards. Results: Phase 1: A combination of analyses identified five positively deviant wards that performed best in the region, outperformed their organisation and performed consistently well over 12 months. Five above average matched comparator wards were also identified. Phase 2: Staff and patient perceptions of safety generally supported the identification of positively deviant wards using Safety Thermometer data, although patient perceptions of safety were less concordant with the routinely collected data. Conclusions: This study tentatively supports a pragmatic method of using routinely collected data to identify positively deviant elderly medical wards; however, it also highlights the various challenges that are faced when conducting the first stage of the positive deviance approach. Trial registration number: UK Clinical Research Network Portfolio (reference-18050).